ANALISIS PENGARUH SPONSORSHIP, PENGALAMAN KONSUMEN, DAN PROMOSI PENJUALAN TERHADAP MINAT BELI KONSUMEN DENGAN KESADARAN MEREK SEBAGAI VARIABEL INTERVENING (Studi pada konsumen ekspatriat penerbangan domestik Garuda Indonesia) - Vitadiani, Ratna; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the influence Integrated Marketing Communication (IMC) consisting of Sponsorship, Customer Experience and Sales Promotion on Purchase Intention with Brand Awareness as a intervening variable (Studies on global consumers of Garuda Indonesia). Sponsorship is a gift of financial support or other forms of finance to the recipient that the recipient remains smooth or strong. Garuda Indonesia suffered downgrades The World's Top 10 Airlines for 3 years in a row. Besides market share for Asian market decreased by -8.78% compared to 2014. Therefore, based on phenomenon that has been described previously, this study aims to analyze the influence of Sponsorship, Customer Experience, and Sales Promotion of the Purchase Intention using Brand awareness as an intervening variable in the study of consumer expatriates Garuda Indonesia. The results showed that the sponsorship positive effect on brand awareness, but the negative effect on purchase intention. Customer experience negatively affect brand awareness, but the positive effect on purchase intention. Influence sales promotion positively to brand awareness and purchase intention. Brand awareness as well as a positive effect on purchase intention.